Characterization and Genomic Analysis of PALS2, a Novel Staphylococcus Jumbo Bacteriophage - Lee, Yoona; Son, Bokyung; Cha, Yoyeon; Ryu, Sangryeol (Frontiers in Microbiology, 2021)
Staphylococcus aureus is an important human pathogen that can be frequently encountered in clinical and food-processing surroundings. Among the various countermeasures, bacteriophages have been considered to be promising alternatives to antibiotics. In this study, the bacteriophage PALS2 was isolated from bird feces, and the genomic and biological characteristics of this phage were investigated. PALS2 was determined to belong to the Myoviridae family and exhibited extended host inhibition that persisted for up to 24 h with repeated bursts of 12 PFU/cell. The complete genome of PALS2 measured 268,746 bp, indicating that PALS2 could be classified as a jumbo phage. The PALS2 genome contained 279 ORFs and 1 tRNA covering asparagine, and the majority of predicted PALS2 genes encoded hypothetical proteins. Additional genes involved in DNA replication and repair, nucleotide metabolism, and genes encoding multisubunit RNA polymerase were identified in the PALS2 genome, which is a common feature of typical jumbo phages. Comparative genomic analysis indicated that PALS2 is a phiKZ-related virus and is more similar to typical jumbo phages than to staphylococcal phages. Additionally, the effective antimicrobial activities of phage PALS2 suggest its possible use as a biocontrol agent in various clinical and food processing environments.